Household Welfare and CO₂ Emission Impacts of Energy and Carbon Taxes in Mexico - Sebastian Renner; Jann Lay; Hannes Greve (German Institute of Global and Area Studies (GIGA), 2017)
We analyse the effects of environmental taxes on welfare and carbon emissions at the household level for the case of Mexico. The integrated welfare-environmental analysis, which is based on a censored energy consumer demand system, extends previous work in two ways. First, the estimation of a full matrix of substitution elasticities allows us to test the necessity of incorporating second-order effects into the welfare analysis. Second, the substitution elasticities derived from the demand system are used to estimate the shortrun CO2 emission-reduction potential. We find that first-order approximations of welfare effects provide reasonable estimates, particularly for carbon taxes. Analog to evidence in other low- and middle-income countries, the taxation of all energy items is found to be regressive, with the exception of motor fuels. The inclusion of CH4 and N2O in a carbon tax regime comes with particularly regressive impacts because of its strong effects on food prices. The analysis of the emission implications of different tax scenarios indicates that short-run emission reductions at the household level can be substantial - though the effects depend on how revenue is recycled. This effectiveness combined with moderate and manageable adverse distributional impacts renders the carbon tax a preferred mitigation instrument. Considering the large effect of food price increases on poverty and the limited additional emission-saving potential, the inclusion of CH4 and N2O in a carbon tax regime is not advisable.
Keywords: 300; climate policy; energy policy; Mexico; poverty; distributional effects